Sexual Violence Crimes And Legal Protection For Victims: Law Number 12 Of 2022 On Sexual Violence Crimes And The Reality Of Handling Sexual Violence Cases In Indonesia - Lestari, Ermina Dwi; G S, Achmad Adi Surya; Noor, Rico Septian (Journal of Law, Politic and Humanities, 2025)
Sexual violence remains a complex social and legal issue and continues to be a significant challenge in Indonesia. Victims of sexual violence often face various forms of injustice, ranging from inadequate legal protection to persistent social stigma. This study aims to analyze the legal protection for victims of sexual violence based on the recently enacted Sexual Violence Crime Law (UU TPKS). The research employs a normative juridical method, using a literature review approach to examine relevant legislation, legal doctrines, and court decisions related to sexual violence crimes. The findings indicate that the UU TPKS provides a clearer and more comprehensive legal framework to protect victims’ rights, including rights to accompaniment, rehabilitation, and compensation. However, in practice, there remain several obstacles such as limited understanding among law enforcement officers, insufficient supporting resources, and stigma and discrimination that hinder victims’ access to justice and protection. In conclusion, although the UU TPKS has brought significant progress in handling sexual violence cases in Indonesia, its implementation still faces challenges that require synergy among the government, victim protection agencies, and society to ensure effective and sustainable protection for victims.